STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN SISWA KELAS III SDIT AR-RASYID KOTA MAKASSAR - Irmayanti Kumara Tungga; Akhmad Syahid; Yusri Muhammad Arsyad; M. Hasibuddin Mahmud; Rosmiati; Akhmad Bazith (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the strategies of Islamic Religious Education (PAI) teachers in improving the Qur’anic reading ability of third-grade students at SDIT Ar-Rasyid Makassar City, to identify supporting and inhibiting factors in its implementation, and to analyze the results of the applied strategies. This research employed a qualitative approach with a descriptive research design. The research subjects consisted of PAI teachers, the principal, and third-grade students. Data were collected through observation, interviews, documentation, and student checklist questionnaires. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The results indicate that Qur’anic reading instruction was implemented using the Ummi Method as the school’s primary approach. The strategies applied included direct instruction, talaqqi (face-to-face guided recitation), practice and repetition (tikrar), as well as habituation and role modeling. The learning process emphasized accurate pronunciation of makharij al-huruf, proper application of tajwid rules, fluency in recitation (tartil), and the development of proper manners in reading the Qur’an. Supporting factors included teacher competence and commitment, school policies, adequate facilities, and parental support. Inhibiting factors included differences in students’ initial abilities, limited instructional time, and insufficient learning assistance at home for some students. The implementation of these strategies demonstrated improvements in reading fluency, accuracy of tajwid, and students’ motivation to read the Qur’an regularly.